Pengaruh Model Pembelajaran Project Based Learning Berbasis STEM Terhadap Kemampuan Literasi Sains Siswa Kelas IV SDN Ambulu 01 - Dinda Masyrofatul Umami (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The scientific literacy abilities of students in Indonesia are still relatively low, as evidenced by the results of the Program for International Students Assessment (PISA) by the International Organization for Economic Cooperation and Development (OECD), so it is necessary to improve the learning process using approaches, models and methods that can influence the quality of the process learning carried out. The application of the Project Based Learning (PjBL) model can be used as a preference for improving scientific literacy skills by providing direct practice, not just theory, so that if problems are found in learning activities, students can immediately analyze the problem, provide critical thinking about the problem, and find a way to solve it. One of the learning models implemented in 21st century learning is the PjBL model based on Science Technology Engineering, Mathematics (STEM). STEM and PjBL have the same goals, namely helping students to easily solve problems with a result in the form of a product so that students are expected to try to develop their skills. This research aims to determine whether there is an effect of implementing the STEM-based PjBL model on the scientific literacy abilities of fourth grade students at SDN Ambulu 01. The research method used is Quasi Experimental Designs experimental research with a Non equivalent Control Group Design pattern. The research was carried out at SDN Ambulu 01 in the odd semester of the 2023/2024 academic year. The research population is class IV students, namely class IVA and IVB with a total of 50 students. Based on the results of all data analysis, it can be concluded that there is an influence of the STEM-based PjBL model on the scientific literacy abilities of class IV students at SDN Ambulu 01.
Reaploud Repository February_Hasyim
Keywords: Project Based Learning Model; STEM; scientific literacy